ANALISIS PERILAKU BIJAK BERMEDIA SOSIAL GENERASI Z BERBASIS NILAI – NILAI PANCASILA SEBAGAI UPAYA PENGUATAN KETAHANAN NASIONAL DI SMP NEGERI 2 NGANTANG - Adi Kurniawan, Prima; Febriana Umbas, Reri; Lailatus Mauludiyah, Siti; Nanik Setyowati, Rr; Maizul Habibah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the high intensity of social media use among Generation Z, which is not always matched by digital literacy skills or the internalization of Pancasila values. This situation has the potential to cause various problems, such as the spread of hoaxes, impolite communication behavior, and the weakening of national resilience in the socio-cultural and ideological dimensions. The objectives of this study are to analyze students’ social media behavior, examine the implementation of Pancasila values in digital activities, and identify their contribution to strengthening national resilience. This study employs a qualitative approach using a case study method at SMP Negeri 2 Ngantang. The research subjects include students, Pancasila Education teachers, Guidance and Counseling teachers, and the school principal. Data collection techniques include observation, in-depth interviews, and documentation, while data analysis utilizes the Miles and Huberman interactive model. The research findings indicate that social media behavior can be divided into positive and negative behaviors. Positive behaviors include using social media as a means of communication, sharing educational information, and expressing creativity. However, negative behaviors such as spreading unverified information, using inappropriate language, and engaging in cyberbullying are still prevalent. The implementation of Pancasila values remains partial and suboptimal. Therefore, strengthening Pancasila-based digital literacy is necessary to shape a generation of youth with strong character and to reinforce national resilience. These efforts can be achieved through the integration of character education into the curriculum, fostering digital ethics, and collaborative oversight between schools and parents. Consequently, students are expected to use social media wisely, critically, and responsibly, thereby contributing to the creation of an ethical digital society and a strong, sustainable national resilience capable of facing the global challenges of the current digital era.